Employment status and health: understanding the health of the economically inactive population in Scotland - Brown Judith; Demou Evangelia; Tristram Madeleine; Gilmour Harper; Sanati Kaveh A; Macdonald Ewan B (BMC, 2012)
Abstract Background Although the association between health and unemployment has been well examined, less attention has been paid to the health of the economically inactive (EI) population. Scotland has one of the worst health records compared to any Western European country and the EI population account for 23% of the working age population. The aim of this study is to investigate and compare the health outcomes and behaviours of the employed, unemployed and the EI populations (further subdivided into the permanently sick, looking after home and family [LAHF] and others) in Scotland. Methods Using data from the 2003 Scottish Health Survey, the differences in health and health behaviours among the employed, unemployed and the subgroups of the EI population were examined. Results Both low educational attainment and residence in a deprived community were more likely in the permanently sick group. The LAHF and the unemployed showed worse self-reported health and limiting longstanding illness compared to the employed but no significant differences were observed between these groups. The permanently sick group had significantly poorer health outcomes than all the other economic groups. Similar to the unemployed and LAHF they are more likely to smoke than the employed but less likely (along with LAHF and 'others') to exhibit heavy alcohol consumption. Interestingly, the LAHF showed better mental health than the rest of the EI group, but a similar mental health status to the unemployed. On the physical health element of lung function, the LAHF were no worse than the employed. Conclusion While on-going health promotion and vocational rehabilitation efforts need to be directed towards all, our data suggests that the EI group is at higher risk and policies and strategies directed at this group may need particular attention.